Cannabis sativa L. Constituents and Their Role in Neuroinflammation - Borgonetti, Vittoria; Governa, Paolo; Montopoli, Monica; Biagi, Marco (Current Bioactive Compounds, 2019)
The interest in Cannabis sativa L. phytocomplex as a medicinal tool is a recently-emerging topic. Neurodegenerative diseases represent a promising field of application for cannabis and its preparations, as most of this pathologic conditions relies on an inflammatory etiology. Several cannabis constituents display anti-inflammatory effects targeting multiple pathways. In this review, a comprehensive overview of the available literature on C. sativa constituents activities in neuroinflammation is given. On the basis that the anti-inflammatory activity of cannabis is not attributable to only a single constituent, we discuss the possible advantages of administering the whole phytocomplex in order to fully exploit the “entourage effect” in neuroinflammatory-related conditions.
Keywords: caryophyllene